Integration of Internet of Things (IoT) on Web-based Chemistry Learning - Annisa Filantropie; Suheryanto Suheryanto; Poedji Loekitowati Hariani (IJFAC (Indonesian Journal of Fundamental and Applied Chemistry), 2023)
The development of science and technology, especially the development of the internet is very rapid today. The world of education, needs to develop learning innovations involving the internet. Internet of Things is one of the innovative technologies that can connect a device or object into a large data base so as to speed up the information process through the power of the internet network. The application of the Internet of Things in high school chemistry learning, especially in the concentration cell potentiometry method, can be used in practicum in school laboratories. The results showed that the combined method of concentration cell potentiometry integrated with the Internet of Things (Pot-IoT) has been proven effective (n-gain = 0.7208) to be used as a learning medium for the practicum of measuring Pb metal in water samples at school.